Liver cirrhosis epidemiology in Chelyabinsk region in 2006-2015 - A. I. Dolgushina; Ye. R. Olevskaya; A. N. Tarasov; M. S. Kazakova; A. Yu. Markina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate epidemiology of the liver cirrhosis (LC) in Chelyabinsk region in 2006-2015. Results. Statistically significant increase of the both total (254.1-391.8 per 100,000 population) and primary (43.3-67.3 per 100,000 population) incidence of the liver diseases was detected. For the 10-year period of monitoring considerable sporadic fluctuations due to the liver diseases were noted. Since 2013 there was a gradual gain in mortality which in 2015 reached 38.35. By 2015 the decline in mortality due to alcohol-induced LC down to 12.6 cases per 100,000 population alone with increase of female proportion up to 42.5% was noted. No less than 50% of LC motility was due to the working-age patients. The basic direct cause of death in LC patients is hepatocellular failure, in 12.84±0.6% of the cases patients died of gastro-intestinal bleeding. Over the half of the cases of annual motility was due to out-hospital cases. By 2015 liver disease associated motility increased by 31.5% and reached 16.91. The number of hospital admissions of patients with liver diseases for the last 10 years decreased and made 95,8±5,5 cases per 100,000 population, the rate of decrease was 8.7%. Conclusions. The negative trends require further improvement of the healthcare management for LC patients. However objectively restrictions in utilization of the available range of treatment-and-prophylactic actions for treatment of LC in the outcome of viral hepatitis (in drug addicts, alcoholic or asocial patients) due to their low treatment compliance.